Translation as Social Action: Brecht’s ‘Political Texts’ in Greek - Asimakoulas, Dimitris (TTR)

(untitled) (Association canadienne de traductologie, 2007)
AbstractThis paper places an influential anthology of Brecht’s texts in the context of the Greek junta (1967-1974). Drawing on the sociological work of Pierre Bourdieu, it shows how the text constitutes an euphemisation of the power of a politically active publisher who opposed the regime with what came to be seen as ‘social art’ by various agents of the publishing field at the time. It also demonstrates how the tactical presentation of the material in the anthology helps map the oppression of the Nazi rule onto the junta while identifying a ‘plural-self’ that opposes symbolic and physical violence.